Prior cesarean section is associated with increased preeclampsia risk in a subsequent pregnancy - Cho, Geum Joon (BMC Pregnancy Childbirth, 2015)
BACKGROUND: To evaluate the impact of a prior cesarean section on preeclampsia risk in a subsequent pregnancy. METHODS: Study data were collected from the Korea National Health Insurance Claims Database of the Health Insurance Review and Assessment Service for 2006–2010. Patients who had their first delivery in 2006 and subsequent delivery between 2007 and 2010 in Korea were enrolled. The overall incidence of preeclampsia during the second pregnancy was estimated and to evaluate the risk of preeclampsia in the second pregnancy, a model of multivariate logistic regression analysis was performed with preeclampsia as the final outcome RESULTS: The risk of preeclampsia in any pregnancy was 2.17%; the risk in the first pregnancy was 2.76%, and that in the second pregnancy was 1.15%. During the second pregnancy, the risk of preeclampsia was 13.30% for women who had developed preeclampsia in their first pregnancy and 0.85% for those who had not. In the entire population, prior cesarean section was associated with preeclampsia risk in their subsequent pregnancy (odds ratio [OR], 1.26; 95% confidence interval [CI], 1.13–1.41). Among women with and without preeclampsia in their first pregnancy, a prior cesarean section was associated with preeclampsia risk in their second pregnancy (OR, 1.35; 95% CI, 1.09–1.67; OR, 1.23; 95% CI, 1.08–1.40, respectively). CONCLUSIONS: Our study showed that cesarean section in a first pregnancy was associated with increased preeclampsia risk in the second pregnancy. These results provide physicians with a preeclampsia risk evaluation method for a second pregnancy that they may aid counseling in patients.